Ценные и вредные элементы в рудах и отходах месторождений черной металлургии; Молодой ученый; № 10 - Азарова С. В. Светлана Валерьевна; Перегудина Е. В. Елена Владимировна; Третьяков А. Н. Алексей Николаевич; Капустина А. А. Анастасия Анатольевна (2015, 2015)
Заглавие с экрана